Multi-Modality Imaging for the Identification of Arrhythmogenic Substrates Prior to Electrophysiology Studies - Gimelli, Alessia; Ernst, Sabine; Liga, Riccardo (Frontiers in Cardiovascular Medicine, 2021)
Non-invasive cardiac imaging is crucial for the characterization of patients candidate to cardiac ablations, both for procedure planning and long-term management. Multimodality cardiac imaging can provide not only anatomical parameters but, even more importantly, functional information that may allow a better risk stratification of cardiac patients. Moreover, fusion of anatomical and functional data derived from non-invasive cardiac imaging with the results of endo-cavitary mapping may possibly allow a better identification of the ablation substrate, also avoiding peri-procedural complications. As a result, imaging-guided electrophysiological procedures are associated with an improved outcome than traditional ablation procedures, with a consistently lower recurrence rate.